Exploring mechanical performance of non-foamed polyurethane-bonded gravel and its pile bearing characteristics under embankments: an experimental and numerical approach - Hu, Xin; Li, Mengliang; Tan, Huiming (Frontiers in Physics, 2024)
Pile supported geogrid-reinforced embankment are widely used to treat soft soil. This paper proposes a novel method for reinforcing foundations using non-foamed polyurethane-bonded gravel (NPBG) porous piles. Through triaxial compression tests, the mechanical properties and strength parameters, such as strength and stiffness, of the polyurethane-bonded gravel material are determined. Finite element numerical simulations are then employed to investigate the bearing characteristics of NPBG porous pile under embankment loads. The experimental results indicate that, under the same confining pressure, the strength and stiffness of the NPBG material are significantly higher than those of plain gravel material, while still retaining large pore characteristics. Increasing the polyurethane content enhances the strength and stiffness of the porous material, but the improvement diminishes as the confining pressure increases. A systematic comparative analysis was conducted on the bearing characteristics of NPBG porous pile versus concrete pile, cement-mixed pile, and gravel pile under embankment in terms of load sharing ratio and settlement deformation. The permeability coefficient and modulus of the pile significantly influence the dissipation rate of excess pore water pressure in the foundation soil. The NPBGP pile exhibited the fastest consolidation speed, effectively controlling total settlement and reducing the proportion of post-construction settlement of the embankment. Compared to concrete pile and cement-mixed pile, the NPBG porous pile has a lower uniform settlement surface height in embankment, making it suitable for low-height embankment accelerated construction projects.